Endodontic treatment of a mandibular first molar with six root canals - A case report - André Luiz da Costa Michelotto; Lisa Yurie Oda; Antonio Batista (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
The mandibular first molar usually has a mesial root with two root canals and a distal root with one or two root canals. However, variations in this morphology, such as multiple root canals, may occur. A 20-year-old male patient presented with a chief complaint of pain and swelling in the left mandibular region. Based on clinical and radiographic exams, the diagnosis of symptomatic apical periodontitis was established. Initially, two root canals in the mesial root and two in the distal root of tooth #36 were located and negotiated using a dental operating microscope. After further exploration, two more root canals were located in the mesial root. The six root canals were prepared. For the final rinse, the irrigant solutions were agitated with an ultrasonic tip. Calcium hydroxide dressing was used, and one month later, the patient presented without signs or symptoms. The root canal filling was performed using the single-cone technique with gutta- -percha cones and bioceramic endodontic sealer. At the 12-month follow-up, a periapical radiograph showed bone repair in the periradicular region. Four root canals in the mesial root of the mandibular first molar represent a rare configuration. The clinician must consider possible anatomical variations of the root canal system and carefully analyze the imaging exams along with clinical observation during treatment so that all canals are located and treated to achieve success.